ATTITUDES IN THE SONG LYRICS OF OLIVIA RODRIGO’S SOUR ALBUM - Putri, Pegita Rianinda; Hapsari, Apriliana; Rosmawati, Devi (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
This research aims to determine the types of attitudes and their manifestation in Olivia Rodrigo’s Sour album. The data used in this research is song lyrics in the form of phrases, clauses, and sentences. This data was obtained from Olivia Rodrigo’s official account on Spotify. The research method used in this research is descriptive-qualitative. The theory of attitude in this research is from Martin and White. This theory is used to identify the types and the manifestation of attitude in Sour. The results show that three kinds of attitudes (affect, judgment, and appreciation) are applied in the song lyrics. Based on the results, affect is the highest type of attitude found, with 74 frequencies (60.66%). Then, judgment is the second type of attitude that appears a lot with 39 frequencies (31.97%). The last type of attitude is appreciation, appearing at least with 9 frequencies (7.37%). Meanwhile, the manifestation, negative manifestation was the highest with 94 frequencies (77.05%), and the positive manifestation with 28 frequencies (22.95%). Affect is the highest type of attitude found in Sour song lyrics. Since more than 60% of the data is found in the form of expressions of feeling undesired, unhappiness, happiness, dissatisfaction, satisfaction, insecurity, and security. Meanwhile, negative manifestation is the highest type of manifestation found. Since 77% of the data is found in the form of expressions of misery, displeasure, disquiet, undesired, criticism, and condemnation.